Back from the brink - Castaldo, Nancy F. (Nancy Fusco), 1962- (Houghton Mifflin Harcourt, 2018)
Chronicles the human intervention used to save seven endangered species, including whooping cranes, bald eagles, and wolves. Discusses the causes of the dwindling populations, and the various recovery efforts that took place to improve the animals' ecosystem.